Computer-controlled Intraligamentary local anaesthesia in extraction of mandibular primary molars: randomised controlled clinical trial - Rodaina H. Helmy; Sarah I. Zeitoun; Laila M. El-Habashy (BMC, 2022)
Abstract Background Local anesthesia (LA) poses a threat in children more than the treatment process itself, so pediatric dentists are always demanding less painful techniques. Computer-controlled Intraligamentary anaesthesia (CC-ILA) is designed to reduce injection pain and side effects of conventional techniques. The present study aims to assess the pain experience using Computer-controlled Intraligamentary anaesthesia (CC-ILA) during injection and its effectiveness in controlling pain during extraction of mandibular primary molars in pediatric patients. Methods This randomized controlled clinical trial includes 50 healthy cooperative children, aged 5-7 years with mandibular primary molars indicated for extraction. They were randomly allocated to two groups according to LA technique: test group received CC-ILA and control group received Inferior alveolar nerve block (IANB). Pain was measured during injection and extraction: physiologically using Heart rate (HR), subjectively using Face-Pain-Scale (FPS), and objectively using Sound-Eye-Motor scale (SEM). Patients were recalled after 24-h to record lip-biting events. Data was collected and statistically analysed. Results A total of 50 children (29 females and 21 males) with mean age 6.10 ± 0.76 participated in the study. There were significantly lower scores in the heart rate in the CC-ILA group during injection (p = 0.04), but no significant difference was recorded between the two groups during extraction (p = 0.17). The SEM and FPS showed significant lower scores in the CC-ILA group during injection (p < 0.0001, p < 0.0001) and extraction (p < 0.0001, p = 0.01) respectively. No children in CC-ILA group reported lip-biting after 24-h compared to 32% in IANB (p < 0.0001). Conclusion CC-ILA provides significantly less painful injections than conventional techniques and has proved to be as effective as IANB during extraction of mandibular primary molars. An important advantage of this technique was the complete absence of any lip/cheek biting events. Trial registration The study was prospectively registered in ClinicalTrials.gov with the identifier: NCT04739735 on 26th of January 2021, https://clinicaltrials.gov/ct2/show/NCT04739735 .